Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum Terhadap Belanja Modal Serta Dampaknya Terhadap Pertumbuhan Ekonomi Daerah (Studi Pada Kabupaten dan Kota di Provinsi Jambi) - Delta Forza; zamzami zamzami; Enggar Diah Puspa Arum (Magister Ilmu Akuntansi Universitas Jambi, 2018)
The purpose of this study is to analyze the effect of Pendapatan Asli Daerah (PAD) and General Allocation Funds to Capital Expenditures, and to test and prove empirically about the influence of Pendapatan Asli Daerah (PAD) and General Allocation Fund (DAU) for both simultaneous and partial, and their impact on regional economic growth. The results showed that the original revenue and general allocation fund affect the capital expenditure in the regency / municipality of Jambi Province. Thus this research proved that PAD and DAU simultaneously have an effect on to Capital Expenditure (BM). Second, the original revenue of the region and the General Allocation Fund affect the capital expenditure in the district / city of Jambi Province. Thus it can be stated that PAD, DAU, and BM have simultaneous and partial effects on economic growth. Keywords: Local Revenue, Capital Expenditure, General Allocation Fund, and Economic Growth.